PELAKSANAAN ASIMILASI BAGI NARAPIDANA TINDAK PIDANA KORUPSI TERKAIT PERATURAN PEMERINTAH NOMOR 99 TAHUN 2012 DI LEMBAGA PEMASYARAKATAN KLAS II A SAMARINDA - Oky Trinsa Harnanto (Universitas 17 Agustus 1945 Samarinda, 2014)
ABSTRACTHaving decided the defendant guilty of corruption by Judge and obtain permanent legal force (inchract) then terpidana criminal acts of corruption is the responsibility of Correctional Facility when executed by the prosecutor. Coaching and treatment for convicted corruption is certainly not the same as convicted - other criminal cases. The age factor and respected positions of corruption convicts causing their social status above from other convict. Implementation of inmates in the construction of Correctional Facility is a way out for the building and also to return the inmate to the right path. One of the construction program undertaken by Correctional Facility is assimilation.The purpose of the government issued Government Regulation No. 99 of 2012 is to provide a sense of security to the community and meet the community's sense of justice. Besides, the government also wants to provide a deterrent for offenders, especially corruption. While the meaning of assimilation is effected Convict construction process with confounding convict in community life. The form of assimilation is education, skills training and social work activities. Based on the above reasons, then the problem can be formulated as follows: The first, How execution for convict assimilation related corruption Government Regulation no. 99 of 2012 in Correctional Facility Class II A Samarinda? Second, What are the barriers and obstacles in the implementation process of assimilation in Correctional Facility Class II A Samarinda? third, how Attempts to overcome constraints - constraints in the implementation of Assimilation in Correctional Facility Class II A Samarinda?From the research and discussion of some of the conclusions obtained are: The first implementation of the assimilation of convict related corruption Government Regulation no. 99 of 2012 in Correctional Facility Class II A Samarinda generally shaped social work with a third party (social institutions). Second, many obstacles encountered, until hamper the smooth assimilation of third parties and the efforts made by the Board of Correctional Facility class II A Samarinda in the launch of assimilation is pretty good although in practice plagued the existing legal framework. Third, the implementation of assimilation for the criminal acts of corruption in the criminal Correctional Facility class II A Samarinda has a maximum, after which an inmate can freely accepted back in the community.